TRAINING OF BACHELORS IN CIRCULAR ECONOMICS IN THE REPUBLIC OF POLAND - Oleksii Sysoiev (Borys Grinchenko Kyiv Metropolitan University, 2021)
The article is devoted to a comprehensive analysis of the curriculum of professional training of bachelors in circular economics at the Silesian Polytechnic of the Republic of Poland. It is shown that such training, which was first introduced in Poland in 2018, has a practice-oriented nature and is aimed at systematic training of bachelors to implement the tasks of the circular economy. The structure of the curriculum, the number of hours devoted to the study of individual subjects and modules of choice, the sequence of study of subjects, types of practical training, project activities of students, forms of study and their ratio are analyzed. The «step» structure of the curriculum complexity of subjects, their professional orientation and study in separate semesters; a significant amount of hours devoted to learning English, the availability of internships with the implementation of the production project. Analysis of curricula for specialists in circular economics at the bachelor's level shows that the professional training of bachelors is practice-oriented using modern learning technologies, in particular the implementation of both training projects and projects in specific industries (production projects). It is concluded that the study of the experience of the Republic of Poland, in particular the analysis of curricula for the training of specialists in circular economics, allows us to use the experience of our neighbors to create, if not a holistic system of training such specialists then at least separate training courses for the implementation of the ideas of a green economy in Ukraine.